Rules vs. Discretion in Cap-and-Trade Programs: Evidence from the EU Emission Trading System - Marina Friedrich; Sébastien Fries; Michael Pahle; Ottmar Edenhofer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Long-term commitment is crucial for the dynamic efficiency of intertemporal cap-and-trade programs. Discretionary interventions in such programs could destabilize the market, and necessitate subsequent corrective interventions that instigate regulatory instability (Kydland and Prescott, 1977). In this work, we provide evidence for this claim from the EU's cap-and-trade program (EU-ETS). We ground our analysis in the theoretical finance literature, and apply a mixed method approach (time-varying regression, bubble detection, crash-odds modelling). We find that the recent EU-ETS reform triggered market participants into speculation, which likely led to an overreaction that destabilized the market. We discuss how the smokescreen politics behind the reform, which manifested itself in complex rules, was crucial for this outcome. We conclude that rules only ensure long-term commitment when their impact on prices is predictable.
Keywords: Q48; Q50; Q56; 330; rules vs. discretion; cap-and-trade; overreaction; allowance pricing